Analisis Sistem Penyimpanan Obat Berdasarkan Standar Pelayanan Kefarmasian Puskesmas di Puskesmas Oesao - Eviyanti Luruk; Dominirsep O. Dodo; Tasalina Y.P. Gustam; Fransiskus G. Mado (Yayasan Literasi Sains Indonesia, 2025)
The storage process is a very important process because it can minimize damage to drugs and ensure the quality and quality of drugs in drug management at Health Center. The drug storage system must be in accordance with pharmaceutical service standards, because inappropriate drug storage can affect the quality of drugs. This research aimed to determine the drug storage system in the Oesao Health Center based on the Pharmaceutical Service Standards of the Health Center. This research was a type of qualitative research with the method used was a case study approach. The case study approach is a more intensive, detailed and in-depth approach to certain problems. Data collection techniques were carried out through in-depth interviews and direct observation of the drug storage system involving 2 informants, namely the person in charge of the pharmacy department and pharmaceutical staff who could provide accurate and reliable information regarding the drug storage system and pharmaceutical service standards. The results of the research showed the indicator of drug storage space regulation has a low percentage with a percentage value of 62.5% in the poor category. Inappropriate storage space can cause changes to the stability of the quality of drugs, and can cause degradation which produces new substances that are toxic. The indicators of drug preparation, drug stock card recording, and drug quality observation were included in the good category with a percentage of 100%. The results of the research showed that the drug storage system at the Oesao Health Center is in accordance with the pharmaceutical service standards of the health center with an average score of 90.62% and was included in the good category.